Microbiological studies of heptahydrate magnesium sulfate obtained from seawater - Carlos Manuel Jiménez-Martínez (Revista Electrónica Dr. Zoilo E. Marinello Vidaurreta, 2019)
Background: heptahydrate magnesium sulfate was obtained by chemical synthesis using seawater. The physicochemical characterization of the product was performed, with specifications according to international standards. The study included the microbiological properties. Objective: to assess the microbiological properties of magnesium sulfate obtained from seawater as a natural source, for pharmaceutical uses. Methods: the microbiological studies were conducted at the Pharmaceutical Laboratory of Oral Liquids (MEDILIP) of the city of Bayamo, Cuba. The analysis of the microbial limits was carried out according to the methodology for non-sterile products described by the 38th United States Pharmacopeia. Different culture media were used. Results: during the study period, the product showed effective resistance to the growth of Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis, Candida albicans, Aspergillus brasiliensis, E. coli, with counts according to the limits established for non-sterile products. Conclusions: the results of the microbiological study showed that synthesized heptahydrate magnesium sulfate fulfills the requirements for its pharmaceutical use.